A Survey of Australian and New Zealand Anaesthetists' Attitudes towards Resuscitation Orders in the Perioperative Setting. Issue 3 (May 2017) - Keon-Cohen, Z.; Myles, P. S.; Story, D. A.
Not for resuscitation (NFR) orders are often suspended during anaesthesia, as perioperative care is believed to inherently involve the need for resuscitation including ventilation support. Recent legislative changes in Australia, New Zealand and the UK have enacted the binding nature of advance care directives (ACDs) in healthcare. National guidelines regarding codes of practice and government strategic plans for implementing advance care planning have reinforced the role for advance care planning in modern healthcare. We surveyed a random selection of Australian and New Zealand consultant and trainee anaesthetists to assess their attitudes towards NFR orders and ACDs in the perioperative setting. We received 290 of 790 distributed surveys (37% response rate). The majority (75%) of respondents reported their knowledge as very low, low, or moderate; 37% never or rarely were treating a patient who had an ACD. Over 90% reported that patient's wishes and understanding of ACDs is important and 89% agreed or strongly agreed that advance care planning should be a routine part of hospital admission for high risk patients. Despite this, only 45% of the respondents would always follow an ACD. Although the majority of respondents to this survey support their use in the perioperative setting, clarification of the specific applicability of ACDs to anaesthesia and their binding nature is required.